Integrating Tasyji’ul Lughah into Arabic Curriculum Development for Creating a Sustainable Linguistic Environment - Fairuz Subakir; Agus Yasin; Siti Nikmatul Rochma; Nur Fera Khalifah; Nuraeni Rahmawati (Education and Sociedad Journal, 2024)
This study examines the integration of Tasyji’ul Lughah into Arabic curriculum development for creating a sustainable linguistic environment at Pondok Modern Darussalam Gontor Putri Campus 1. Using a qualitative case study approach, the research explored how the program was integrated into curriculum practices and contributed to strengthening bi’ah lughawiyyah within the pesantren environment. Data were collected through in-depth interviews, participant observation, and documentation involving curriculum coordinators, Arabic teachers, language supervisors, student language organizers, and female students. The data were analyzed interactively through data condensation, data display, and conclusion drawing. The findings reveal that Tasyji’ul Lughah functions not only as a language motivation program but also as an integrative curriculum strategy connecting formal Arabic instruction with authentic communicative practices in students’ daily lives. The integration was reflected in language regulations, vocabulary habituation, communicative interaction, and institutional language culture. The study further found that sustainable bi’ah lughawiyyah was strengthened through institutional ideology, peer interaction, and continuous language exposure, which positively affected students’ communicative competence, speaking confidence, and intrinsic motivation. This study contributes to Arabic curriculum innovation discourse by offering an integrative model for developing sustainable Arabic linguistic ecosystems in Islamic boarding schools.